2021
DOI: 10.1155/2021/7844472
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] CNN‐LSTM Hybrid Model for Kinematic Feature Analysis and Parabolic Radian Prediction in Basketball Videos

Abstract: With the improvement of living standards around the world, people's love for sports has also increased; basketball is especially loved by people. It is of great importance to provide sound motor instruction for basketball. To this end, this paper comprehensively investigates the dependence between the optimal release conditions and the corresponding shooting arm movements in basketball players. We carry out kinematic feature analysis of basketball sports videos, propose a hybrid CNN-LSTM model that can predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…CNN-LSTM hybrid model has been successfully used in tasks requiring sequence learning of visual features [ 45 ], like video classification and activity recognition in videos [ 18 , 46 ]. Our task was similar to activity classification in videos that predict which activity is being performed by analyzing visual changes over time.…”
Section: Image Acquisition and Annotationmentioning
confidence: 99%
See 1 more Smart Citation
“…CNN-LSTM hybrid model has been successfully used in tasks requiring sequence learning of visual features [ 45 ], like video classification and activity recognition in videos [ 18 , 46 ]. Our task was similar to activity classification in videos that predict which activity is being performed by analyzing visual changes over time.…”
Section: Image Acquisition and Annotationmentioning
confidence: 99%
“…This problem can be solved by using recurrent neural networks (RNN). In particular, long short-term memory (LSTM) has a very good performance in analyzing dynamic information [ 18 20 ]. Conjunction of CNN and LSTM could integrate spatial and temporal information from processing signals to help predict plant growth status more precise.…”
Section: Introductionmentioning
confidence: 99%
“…The convolution operation is performed by sliding the kernel over the input matrix, and at each position, the element-wise multiplication and summation are computed as described in the formula [29]. For 1D convolutions, the mathematical formulation is similar, with the kernel sliding along a one-dimensional sequence, such as a time series or text data [30].…”
Section: A Mathematical Formulation Of Convolutionsmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%